2020
DOI: 10.3389/fmicb.2020.01574
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Microbial Community Characteristic and Its Driving Factors in a Copper Tailings Dam in the Chinese Loess Plateau

Abstract: A combined soil bacterial and fungal community survey was conducted for a copper tailings dam in the Chinese Loess Plateau. We investigated the seasonal differences in the composition and function of soil microbial community to examine the key environmental factors influencing soil microorganisms during restorative ecological processes. Significant seasonal differences were found in the community structure of both bacterial and fungal communities. Bacterial community abundance and fungal community (Shannon ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
6
9
0
Order By: Relevance
“…Dominant fungal phyla included Ascomycota, Basidiomycota, and Mortierellomycota. Similar results were reported by other researchers ( Bahram et al, 2020 ), wherein Ascomycota and Basidiomycota were the ubiquitously dominant phyla ( Tian et al, 2017 ; Zeng et al, 2019 ; Zhong et al, 2020 ) and the primary decomposers of litter and soil organic matter ( Jia et al, 2020 ). The relative abundance of Ascomycota was relatively lower and that of Basidiomycota was relatively higher in the broadleaf forest soil, which was possibly due to the higher carbon to nitrogen ratio.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Dominant fungal phyla included Ascomycota, Basidiomycota, and Mortierellomycota. Similar results were reported by other researchers ( Bahram et al, 2020 ), wherein Ascomycota and Basidiomycota were the ubiquitously dominant phyla ( Tian et al, 2017 ; Zeng et al, 2019 ; Zhong et al, 2020 ) and the primary decomposers of litter and soil organic matter ( Jia et al, 2020 ). The relative abundance of Ascomycota was relatively lower and that of Basidiomycota was relatively higher in the broadleaf forest soil, which was possibly due to the higher carbon to nitrogen ratio.…”
Section: Discussionsupporting
confidence: 90%
“…The change in vegetation areas under different land utilization methods might change microbial community structure and function of topsoil ( Bahram et al, 2020 ). In this study, the dominant phyla of bacteria mainly included Actinobacteriota, Proteobacteria, and Acidobacteriota, similar to that reported in earlier studies ( Chu et al, 2010 ; Li Y. Y. et al, 2014 ; Jia et al, 2020 ). We found that vegetation reconstruction modes significantly affected the dominant soil bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Ascomycota was found to be the dominant phylum in the soil of evergreen and deciduous forests in northeast Thailand [ 64 ]. Moreover, these results were supported by the findings of previous studies, which reported that Ascomycota was associated with high levels of distribution and abundance in global soil samples [ 66 , 67 , 68 , 69 , 70 ]. Our findings are similar to the findings of a number of previous studies [ 34 , 70 , 71 , 72 , 73 , 74 , 75 ] that found that Inocybe, Lactarius, Meliniomyces , and Russula are ectomycorrhizal-dominated fungal communities in the soil samples of tropical, temperate and boreal forests.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the soil bacterial community has undergone substantial seasonal variations as a result of temperature (Abed et al, 2015). During warm times, the soil bacterial community richness index (ACE and Chao1) and diversity index (Shannon) values were the greatest (i.e., summer; Jia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%